2017
DOI: 10.1161/jaha.116.005307
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cirrhosis in Patients With Atrial Fibrillation: Would Oral Anticoagulation Have a Net Clinical Benefit for Stroke Prevention?

Abstract: BackgroundPatients with liver cirrhosis have been excluded from randomized clinical trials of oral anticoagulation therapy for stroke prevention in atrial fibrillation. We hypothesized that patients with liver cirrhosis would have a positive net clinical benefit for oral anticoagulation when used for stroke prevention in atrial fibrillation.Methods and ResultsThis study used the National Health Insurance Research Database in Taiwan. Among 289 559 atrial fibrillation patients aged ≥20 years, there were 10 336 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 23 publications
4
88
0
5
Order By: Relevance
“…ILF is associated with increased bleeding risk and has been included in a bleeding risk scoring system for assessing the 1‐year risk of major bleeding associated with warfarin therapy in patients with AF 2, 3, 4. In addition, hepatitis‐related chronic liver disease and cirrhosis are prevalent in Asia and are associated with higher risks of ischemic stroke, portal vein thrombosis, intracranial hemorrhage, and variceal bleeding 5, 6, 7, 8. Non–vitamin K antagonist oral anticoagulant (NOAC) represents a major advance in stroke prevention for AF patients, offering at least equivalent efficacy and less bleeding compared with warfarin 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…ILF is associated with increased bleeding risk and has been included in a bleeding risk scoring system for assessing the 1‐year risk of major bleeding associated with warfarin therapy in patients with AF 2, 3, 4. In addition, hepatitis‐related chronic liver disease and cirrhosis are prevalent in Asia and are associated with higher risks of ischemic stroke, portal vein thrombosis, intracranial hemorrhage, and variceal bleeding 5, 6, 7, 8. Non–vitamin K antagonist oral anticoagulant (NOAC) represents a major advance in stroke prevention for AF patients, offering at least equivalent efficacy and less bleeding compared with warfarin 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the benefit of anticoagulation systematically or in a randomized fashion. Kuo et al evaluated liver disease patients with CHA 2 DS 2 ‐VASc score ≥2 in the setting of AF and showed a reduction in ischemic stroke events in patients treated with warfarin compared with those with and without antiplatelet therapy, notably without increased intracranial hemorrhage 16. However, an increased risk of hemorrhagic stroke and intracranial hemorrhage has been reported in patients with cirrhosis as compared with those without,17, 18 and in 1 study was reported to be higher than ischemic stroke risk 19.…”
Section: Discussionmentioning
confidence: 99%
“…Major bleeding is increased in VHD patients treated with rivaroxaban.Bioprosthetic heart valvePokorney SD, 2015 [43]ApixabanNo difference in risk of stroke and major bleeding between the apixaban and warfarin group.Carnicelli AP, 2017 [44]Edoxaban(high-dose arm)0.37 (0.1–1.42)0.5 (0.15–1.67)Higher-dose edoxaban has similar rates of stroke and major bleeding compared with warfarin . Lower-dose edoxaban has similar rates of stroke but lower rates of major bleeding.Edoxaban(low-dose arm)0.53 (0.16–1.78) 0.12 (0.01–0.95) Concomitant PCIDewilde WJ, 2013 [46]warfarin plus clopidogrelIn comparison to triple therapy (warfarin plus aspirin and P2Y12 inhibitor). HR   =   0.60 (0.38–0.94) for secondary endpoint (death, myocardial infarction, stroke, target-vessel revascularization, and stent thrombosis) HR   =   0.36 (0.26–0.50) for any bleeding.Cannon CP, 2017 [47]Dabigatran 150 mg plus P2Y12 inhibitorIn comparison to triple therapy (warfarin plus aspirin and P2Y12 inhibitor).Dual-Therapy Group (110 mg), HR   =   0.52 (0.42–0.63) ; Dual-Therapy Group (150 mg), HR   = 0.72 (0.58–0.88) for major or clinically relevant non-major bleeding events.Dual-Therapy Groups (Combined), HR = 1.04 (0.84 to 1.29) for risk of thromboembolic events.Dabigatran 110 mg plus P2Y12 inhibitorGibson CM, 2016 [48]Rivaroxaban 15 mg plus P2Y12 inhibitorIn comparison to warfarin plus aspirin and P2Y12 inhibitor.Low dose Rivaroxaban Group, HR = 0.59 (0.47–0.76); very low dose Rivaroxaban Group, HR   = 0.63 (0.50–0.80) for clinically significant bleeding.Low dose Rivaroxaban Group, HR = 1.08 (0.69–1.68); very low dose Rivaroxaban Group, HR = 0.93 (0.59–1.48) for major adverse cardiovascular event (a composite of death from cardiovascular causes, myocardial infarction, or stroke)rivaroxaban 2.5 mg plus aspirin and P2Y12 inhibitorCirrhosisKuo L, 2017 [49]Warfarin 0.76 (0.58–0.99) 1.27 (0.82–1.95)Warfarin use was associated with a lower risk of ischemic stroke and positive NCB compared with non-treatment.CKD = chronic kidney disease; CI = confidence interval; eGFR = estimated glomerular filtration rate; ESRD = end-stage renal disease; HR = Hazard ratio; ICH = intracranial hemorrhage; NCB = net clinical benefit; NOAC = Non-Vitamin K antagonist oral anticoagulants; OAC = oral anticoagulants; PCI = percutaneous coronary intervention; RR = relative risk.Bold and italic values indicate statistically significant difference between two groups.…”
Section: Introductionmentioning
confidence: 99%